EVALUATION OF WASTE MANAGEMENT POLICY IN PALU CITY - M. Kafrawi Al-Kafiah Samsu; La Husen Zuada; Moh. Rendy (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Tadulako, 2020)
This research aims to find out the evaluation of waste management policiy in Palu City and how to counteract them to be as expected in Regional Regulations. Type of research was qualitative by using descriptive methods. Data collection techniques covered in-depth interviews and observations. The results of research related to the evaluation of waste management policy in Palu city have been carried out but it’s not maximum because there were problems in evaluation criteria such as effectiveness, efficiency, and adequacy. Effectiveness has not been achieved because of the lack of control from the concerned parties and public awareness in waste management. Efficiency has not been achieved because of the behaviour and public awareness of the environment is low. In addition, the specified waste disposal operational time has not been fully adhered to the community, while adequacy criteria have not been able to solve environmental hygiene and health problems due to the presence of TPS, only causing a bad smell in the surrounding environment so that it can indirectly affect the level of cleanliness and public health.